2023
DOI: 10.1002/jaba.979
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of competing stimulus assessments: A summary of 35 consecutively encountered cases

Abstract: Competing stimulus assessments (CSAs) are designed to identify stimuli that reduce challenging behavior through competition with its maintaining reinforcers. Recently, Haddock and Hagopian (2020) found that over 92% of CSAs described in published studies identified at least one high-competition stimulus (i.e., a stimulus correlated with at least an 80% reduction in challenging behavior). The current study describes the outcomes of CSAs in a retrospective consecutive controlled case series study of 35 cases (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…Results of this report provide some preliminary insight into situations when an A‐CSA fails to yield an item that competes with problem behavior, when a) reinforcers are limited, b) it is not appropriate to shape an alternative response (e.g., not appropriate to encourage skin picking or property destruction to reinforce discarding pica items; Hagopian, Rooker et al., 2011; Hagopian, González et al., 2011), or c) if pica (and/or attempts) persists despite high levels of engagement with preferred item(s). One solution could be additional applications of the A‐CSA with new items (e.g., Laureano et al., 2023). This may be especially beneficial for those with limited exposure to enriched environments.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this report provide some preliminary insight into situations when an A‐CSA fails to yield an item that competes with problem behavior, when a) reinforcers are limited, b) it is not appropriate to shape an alternative response (e.g., not appropriate to encourage skin picking or property destruction to reinforce discarding pica items; Hagopian, Rooker et al., 2011; Hagopian, González et al., 2011), or c) if pica (and/or attempts) persists despite high levels of engagement with preferred item(s). One solution could be additional applications of the A‐CSA with new items (e.g., Laureano et al., 2023). This may be especially beneficial for those with limited exposure to enriched environments.…”
Section: Discussionmentioning
confidence: 99%
“…The CSA data were sourced from four CCCS studies (Frank-Crawford et al, 2023;Hagopian et al, 2015Hagopian et al, , 2020Laureano et al, 2023). These studies describe CSA outcomes (or outcomes of the free access condition of the augmented CSA) for 31 CSA applications targeting either Subtype 1 (n = 14) or Subtype 2 (n = 17) SIB.…”
Section: Sources Of Clinical Datamentioning
confidence: 99%
“…The ETBD is a computational algorithm that models how behavior changes dynamically as a function of selection by the contingencies of reinforcement based on Darwinian evolutionary processes. The ETBD is a principle-first complexity theory, based on a selectionist account of behavior that describes how behavior is changed as a Laureano et al (2023). For the AOs (bottom panels), each stimulus trial represents 500 generations.…”
Section: Conceptual Considerations When Applying the Etbdmentioning
confidence: 99%
“…However, CSAs are not universally effective in identifying HC stimuli. For example, Laureano et al (2023) reported on outcomes from 34 CSA applications across 22 consecutively encountered cases of individuals with automatically maintained SIB. 1 One or more HC stimuli were identified in only 44.1% of these applications.…”
mentioning
confidence: 99%
“…Given that Hagopian et al (2015) found that CSAs that did not include these augmentative tactics effectively identified HC stimuli for all individuals with Subtype 1 SIB, it is reasonable to assume that the tactics included in the A-CSA may not be necessary for those with this subtype. Thus, the purpose of the current study 1 Laureano et al (2023) report on outcomes for individuals with socially maintained challenging behavior and automatically maintained challenging behavior. Because the focus of the current paper is on automatically maintained behavior, we have summarized outcomes from the subset of individuals in Laureano et al that presented with automatically maintained behavior.…”
mentioning
confidence: 99%